1976
DOI: 10.1159/000122630
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Continuous Light and Darkness, and of Pinealectomy, Adrenalectomy and Gonadectomy on Uptake of <sup>3</sup>H-Serotonin by the Suprachiasmatic Nuclear Region of Male Rats

Abstract: Rats exposed to continuous light show no significant differences in serotonin (5-HT) uptake by the suprachiasmatic nuclear region (SNR) at 10.00 and 22.00 L, while in continuous darkness, the uptake at 10.00 D is significantly higher than uptake at 22.00 D. In consideration of the role of the suprachiasmatic nucleus in light-mediated control of neuroendocrine activity, this suggests endogenous generation or control of this uptake rhythm. An effect of sham-pinealectomy in decreasing 5-HT uptake was found, but c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

1979
1979
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Compared to the fluctuation of adrenal E in Con and NO-V birds, a loss of the nocturnal elevation of E was noted in the adrenals of SO-V chicks. Similar to this finding, effects of shampinealectomy long after surgery have been reported by several authors (Meyer and Quay, 1976;Gorray and Quay, 1978;Banerji et al, 1980;Kachi et al, 1979Kachi et al, , 1980Banerji and Quay, 1986). Although the underlying mechanism for the effects of sham-pinealectomy on adrenal catecholamines remain to be elucidated, it might be that the surgical stress or trauma has repercussions on the adrenomedullary nerve endings (Kachi et al, 1988).…”
Section: Discussionsupporting
confidence: 84%
“…Compared to the fluctuation of adrenal E in Con and NO-V birds, a loss of the nocturnal elevation of E was noted in the adrenals of SO-V chicks. Similar to this finding, effects of shampinealectomy long after surgery have been reported by several authors (Meyer and Quay, 1976;Gorray and Quay, 1978;Banerji et al, 1980;Kachi et al, 1979Kachi et al, , 1980Banerji and Quay, 1986). Although the underlying mechanism for the effects of sham-pinealectomy on adrenal catecholamines remain to be elucidated, it might be that the surgical stress or trauma has repercussions on the adrenomedullary nerve endings (Kachi et al, 1988).…”
Section: Discussionsupporting
confidence: 84%
“…It remains possible, therefore, that these two tissue components are affected differently under various surgical manipulations of the pineal and/or melatonin adminstration. This is clearly suggestive from our present experiment in which the shamoperated group receiving a low dose of melatonin had significantly lower adrenal DBH activity compared to the matched PX group (i.e., PX + 25 pg melatonin) although the changes in adrenal weight were not significantly different [Quay et al, 19821. Diverse effects of sham-pinealectomy long after surgery and after all overt sequelle of the operation had disappeared have been reported in recent years [Meyer and Quay, 1976;Gorray and Quay, 1978;Banerji et al, 19801. For example, in many cases, sham-pinealectomy and pinealectomy have been found to produce similar results. A plausible explanation for this has been provided by Frowein and Lapin [1979] who found that surgery performed under strong white light led to a long-lasting depression in pineal content of melatonin in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic 5-HT activity has been related to photosexual responses in mammals (Meyer and Quay 1976) and birds (Elhalawani et al 1978), the control of endocrine rhythms (Kordon et al 1978;Scapagnini et al 1978) and to the transmittance of day-night information in ferrets (Yates and Herbert 1976). A hypothalamic serotonergic system is implicated in the regulation of the secretion of prolactin (Olivereau 1978a;James and Wigham 1984), MSH (Olivereau 1978b) and gonadotropin (Groves 1984) from the pituitary of teleosts; all of which are influenced by environmental light regimes.…”
Section: Discussionmentioning
confidence: 99%
“…In higher vertebrates, hypothalamic monoamines are implicated in the control of endocrine rhythms (Kordon et al 1978;Scapagnini et al 1978). Circadian activity of hypothalamic serotonin (5-HT) is related to transmission of day length information in ferrets (Yates and Herbert 1976) and a serotonergic mechanism is suggested to be involved in photosexual responses in mammals (Meyer and Quay 1976) and birds (Elhalawani et al 1978).…”
Section: Introductionmentioning
confidence: 99%